Paleoenvironmental recovery after the Cretaceous/Paleogene boundary crisis: Evidence from the marine bidart section (SW France) - Alegret, L; Kaminski, MA; Molina, E (SEPM-SOC SEDIMENTARY GEOLOGY, 2004)
The study of Upper Cretaceous and Lower Paleogene benthic foraminifera from the Bidart section (SW France) provides detailed data on the paleobathymetry as well as paleoenvironmental conditions across the Cretaceous /Paleogene (K/Pg) boundary. A quantitative analysis of benthic foraminiferal assemblages from the Upper Maastrichtian Abathomphalus mayaroensis Biozone and the Danian Guembelitria cretacea, Parvularugoglobigerina eugubina, and Parasubbotina pseudobulloides Biozones was performed. Benthic foraminifera indicate that the upper Maastrichtian and lower Danian sediments at Bidart were deposited in the upper-middle part of the slope.Benthic foraminiferal assemblages indicate mesotrophic conditions during the late Maastrichtian and a strong decrease in the food supply to the sea floor coincident with the K/Pg boundary. This change in the trophic regime was related to the collapse of the food web triggered by the mass extinction of calcareous primary producers. Benthic assemblages in the lower Danian are strongly dominated by few species, and suggest that primary productivity was dominated by blooms of non-calcareous primary producers, creating a stressful environment for the benthic fauna. The faunal turnover, together with the geochemical evidence, is compatible with an asteroid impact scenario. Benthic foraminiferal assemblages suggest that primary productivity had not completely recovered more than 200 kyr after the K/Pg boundary event.